Comprehensive three-dimensional hydrodynamic and thermal modeling of steady-state operation of a flat grooved heat pipe. (March 2023) - Gökçe, Gökay; Kurt, Cem; Odabaşı, Gülnihal; Dursunkaya, Zafer; Çetin, Barbaros
Abstract: Mathematical modeling of grooved heat pipes is a challenging task since multiple coupled physical phenomena such as phase change, free-surface flow and heat transfer are involved. Moreover, the fact that the shape of the liquid–vapor interface in the heat pipe is unknown a priori requires simultaneous determination of the interface variation as a part of the solution procedure, a capability currently not addressed in commercially available engineering CFD tools. In this study, a multi-dimensional and multi-scale computational model is presented to gain a comprehensive understanding of the underlying physics of grooved heat pipes. The computational model is based on an iterative scheme for the solution of 3D heat transfer and liquid flow, interface phase change heat transfer (evaporation and condensation) and shape of the interface. The model is implemented using three different methodologies two of which utilize commercial engineering CFD software. The results are verified for a problem previously studied in the literature which indicates the robustness of our computational approach. Highlights: 3D hydrodynamic and thermal model of a grooved heat pipe using three methodologies. A multi-dimensional and multi-scale computational model is presented including phase change. An iterative scheme for the determination of the shape of the liquid–vapor interface.